EDUKASI PASAR MODAL BAGI PELAJAR HINTERLAND DI PULAU BULUH BATAM - Erni Yanti Natalia; Mortigor Afrizal Purba; Neni Marlina Br Purba; Rikson Pandapotan Tampubolon (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2026)
One way to build a country's economy is through capital market movements. Socialization and education continue to be provided to regions related to the correct way and mechanism of investment. This activity is carried out in various ways, namely through electronic media, social media, to universities through stock exchange seminars, to certain institutions, and even to schools to students. SMAN 11 Batam is a school that is geographically separated from Batam City or commonly called Hinterland. The service team is interested in providing education and socialization to students in the hinterland area due to the lack of information they get through lessons at school and to foster interest in investing among students from an early age. After participating in the counseling, participants were very enthusiastic about receiving education on the importance of optimizing the millennial generation and capital market education for students. Participants will understand and understand more about the benefits and role of the Capital Market for the Indonesian economy, as well as how to transact in the Capital Market.